After the Text Byzantine Enquiries in Honor of Margaret Mullett - James, Liz; Nicholson, Oliver; Scott, Roger (Birmingham Byzantine and Ottoman Studies, 2022)
Byzantine Literature, Literature, Byzantine History, History, Poetry, Greek Literature, Byzantine Culture, Late Antique Literature, Medieval Literature, Classical Literature, and Hagiography